Optimal base station selection based on dynamic programming for reprogramming in mine wireless network - Jiang-hong HAN; Zhang-ling DUAN; Xing WEI; Yang LU; Jian-jun ZHANG (Tongxin xuebao)
The nodes of large-scale wireless network which widely used in safety-critical systems often update new code,the way of wireless reprogramming is efficiency and flexibility.The problem of selecting the optimal base station when nodes uniformly distributed in mine wireless network environment and all other nodes were reprogrammed efficiency.Firstly,the model of base station selecting was established by covering process of reprogramming.Then the problem was transformed into solving the minimum of longest non-cyclic path between node and base station in undirected circulant graph.Finally,the optimal algorithm based on dynamic programming which included optimal substructure and overlapping subproblems was proposed.Numerical analysis and experimental results show that the time consumption of proposed algorithm is more stable than other optimal algorithm when the complexity of network is increased sharply.